PENGARUH SLOW DEEP BREATHING TERHADAP TEKANAN DARAH LANSIA HIPERTENSI YANG MENDAPAT SENAM LANSIA DI DESA STUNGKIT, BINJAI TAHUN 2020 - DANIEL SURANTA GINTING (Jurnal Penelitian Keperawatan Medik, 2020)
Hypertension in the elderly continues to increase. According to WHO statistical data in 2018 there were 1 billion people in the world suffering from hypertension. There are several precautions that can be done by the elderly to avoid hypertension, namely : balance nutrition, get rid of smoking, avoid stress, monitor blood pressure, and exercise regularly. Regular exercise can be done by means of physical exercises, namely by exercising the elderly and slow deep breathing. The purpose of this study was to determine whether there is an effect of slow deep breathing on blood pressure in elderly hypertensive receiving elderly exercise. This study used a quasi experimental design with one group pre-post test design. This research was conducted in Pustu Stungkit village, Wampu district, Langat regency, North Sumatra. The research sample was 26 respondents with the sampling technique using purposive sampling. Research instrument using blood pressure observation sheet,spigmomanometer, stop watch. Data processing techniques using the wilcoxon test. The results showed that the average systolic blood pressure before treatment was 158,00 mmhg and diastole 96,00mmhg. And systolic blood pressure after treatment was 148,50 mmhg and diastole 80 mmhg. With a significance value of 0,002 or p<0,05. The conclusion shows that there is an effect of slow deep breathing on the blood pressure of hypertensive elderly who receive exercise in the elderly in the village of stungkit, Binjai.